The Interplay between Digitalization and Competitiveness: Evidence from European Countries - Gheorghe Hurduzeu; Iulia Lupu; Radu Lupu; Radu Ion Filip (Societies, 2022)
In modern societies, digitalization plays a tremendously important role for people and businesses. Apart from an economic representation, competitiveness characterizes a society from political, cultural, or human points of view. In this article, we aim to highlight the role of digital development from a competitiveness perspective, as there are few studies related to this relationship. The empirical investigation is based on panel data analysis for European Union countries for 2017–2022, considering the digital economy and society index (DESI) and the index developed by International Institute for Management Development (IMD), respectively IMD world competitiveness index. The results obtained are reported both for general indices and for the components of DESI, presented separately for the groups of Central and Eastern European countries and Western European countries. They indicate different influences for the two groups of countries, with only a few common aspects. The most obvious is the case of skilled labor. This aspect demonstrates the link between the various dimensions of digitalization and changes in human capital development strategies, as they appear in the specialized literature.